Radiotherapy Quality Assurance for Head and Neck Squamous Cell Carcinoma - Van Gestel, Dirk; Dragan, Tatiana; Gregoire, Vincent; Budach, Volker (Frontiers in Oncology, 2020)
The impact of radiotherapy (RT) quality assurance (QA) has been demonstrated by numerous studies and is particularly important for head and neck cancer (HNC) treatment due to the complexity of RT target volumes in this region and the multiple adjacent organs at risk. The RT planning process includes many critical steps including interpretation of diagnostic imaging, image fusion, target volume delineation (tumor, lymph nodes, and organs at risk), and planning. Each step has become highly complex, and precise and rigorous QA throughout the planning process is essential. The ultimate aim is to precisely deliver radiation dose to the target, maximizing the tumor dose and minimizing the dose to surrounding organs at risk, in order to improve the therapeutic index. It is imperative that RT QA programs should systematically control all aspects of the RT planning pathway and include regular end-to-end tests and external audits. However, comprehensive QA should not be limited to RT and should, where possible, also be implemented for surgery, systemic therapy, pathology, as well as other aspects involved in the interdisciplinary treatment of HNC.